KEADILAN PROSEDURAL PARTISIPATIF DAN DUKUNGAN SERIKAT PEKERJA TERHADAP KEPUASAN KERJA - Asep Qustolani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2019)
This study aims to determine how the influence of Justice Procedural Participatory and Trade Union Support to Job Satisfaction of employees at UD. Putra TS Majalengka. The hypothesis proposed in this research is that Participatory Procedural Justice and Trade Union Support have a significant effect on Job Satisfaction,so that population in this research is UD Putra TS Super Market Majalengka taken as respondents that amounted to 100 people. The research method used survey method with descriptive approach verifikatif. The analysis tools used in this study are classical assumption, multiple regression analysis, coefficient of determination, and hypothesis test for partial test using t test and simultaneous test using F test. The results showed that participative procedural justice and union support had a significant effect on employee job satisfaction which means better procedural paticifative justice in the employees and the better the union support to employees will increase employee job satisfaction.